Effects of physiological fatigue on basketball shooting performance: the moderating role of attentional focus - Luo, Yuanyuan; Cao, Yingying; Li, Shuairan; Shi, Yan; Chen, Peng (Frontiers in Psychology, 2025)
ObjectivesThis study examined the moderating effect of attentional focus on basketball shooting performance under varying fatigue levels.MethodsA 2 (Attentional Focus: External vs. Internal) × 3 (Fatigue Level: No Fatigue, Moderate Fatigue, Severe Fatigue) within-subject design was employed. Thirty male basketball players (mean age: 20.1 ± 0.3 years) completed 20 standardized free-throw attempts under each condition. Shooting accuracy was recorded, and repeated measures ANOVA was performed to analyze main and interaction effects.ResultsSignificant main effects were observed for attentional focus [F (1,29) = 8.15, p = 0.008] and fatigue level [F (2,58) = 26.32, p < 0.001] along with a significant interaction effect between attentional focus and fatigue level [F (2,58) = 4.27, p = 0.018]. Shooting accuracy under external focus (75.0%) was significantly higher than under internal focus (65.0%). Under severe fatigue, external focus resulted in a 15% higher shooting accuracy than internal focus, with this advantage increasing as fatigue levels intensified.ConclusionFatigue impairs basketball shooting performance; however, adopting an external attentional focus can mitigate its negative impact, particularly under severe fatigue conditions.